Management of Kshudra Kushta (Tinea Cruris) through Ayurveda-A Case Report. - Dixit, Neha; Choudhary, Poonam (International Research Journal of Ayurveda & Yoga, 2023)
Fungal infections are among the most common skin disease throughout the world. “Tinea cruris” infections are fungal infection that affects the groin, perineal and Peri-anal region. All the skin disease in Ayurveda have been discussed under broad heading of Kushta. Management of Kushta roga includes Shodhana, Shaman and Bahiparimarjana chikitsa. A 30 years old female patient presented to Prasuti Tantra Evum Stree Roga OPD, in June 2022 with complaining of itching in perineal region. On the basis of clinical examination, the case diagnosis was made as Kshudra Kushta w.s.r. Tinea Cruris. This paper highlights a case study of Kshudra kushta w.s.r. Tinea Cruris treated with ayurvedic principles.